PENGARUH PENGETAHUAN BAHAN TAMBAHAN PANGAN TERHADAP PEMILIHAN MAKANAN JAJANAN SISWA SEKOLAH MENENGAH KEJURUAN - Khasanah, Uswatun; Setyaningsih, Rina (KELUARGA: Jurnal Ilmiah Pendidikan Kesejahteraan Keluarga, 2024)
The purpose of this study was to determine: (1) knowledge of food additives in students (2) selection of student snacks and (3) the effect of knowledge of food additives on student selection of snack foods. This research includes the type of ex-post facto research. Methods of data collection using questionnaires and documentation. Data analysis techniques using statistical and correlational tests using normality and linearity tests. The results showed that (1) the students' knowledge of food additives was mostly in the high criteria with a relative frequency of 70.91%. (2) The selection of student snacks is mostly in the high criteria with a relative frequency of 67.27%. (3) Knowledge of food additives affects the selection of student snacks, with an r count of 0.653 > 0.266. The coefficient of determination (R2) is 0.426, meaning that the contribution made by variable X to variable Y is 42.6%, while the remaining 57.4% is influenced by other factors not discussed in this study. Keywords: Knowledge, Food Additives, Snack Foods